The General Practice Assessment Questionnaire (GPAQ) – Development and psychometric characteristics - Nicola Mead; Peter Bower; Martín Roland (2008)
Continual quality improvement in primary care is an international priority. In the United Kingdom, the major initiative for improving quality of care is the Quality and Outcomes Framework (QoF) of the 2004 GP contract. Although the primary focus of the QoF is on clinical care, it is acknowledged that a comprehensive assessment of quality also requires valid and reliable measurement of the patient perspective, so financial incentives are included in the contract for general practices to survey patients' views. One questionnaire specified for use in the QoF is the General Practice Assessment Questionnaire (GPAQ). This paper describes the development of the GPAQ (with post-consultation and postal versions) and presents a preliminary examination of the psychometric properties of the questionnaire.Description of scale development and preliminary analysis of psychometric characteristics (internal reliability, factor structure), based on a large dataset of routinely collected GPAQ surveys (n = 190,038 responses to the consultation version of GPAQ and 20,309 responses to the postal version) from practices in the United Kingdom during the 2005-6 contract year.Respondents tend to report generally favourable ratings. Responses were particularly skewed on the GP communication scale, though no more so than for other questionnaires in current use in the UK for which data were available. Factor analysis identified 2 factors that clearly relate to core concepts in primary care quality ('access' and 'interpersonal care') that were common to both version of the GPAQ. The other factors related to 'enablement' in the post-consultation version and 'nursing care' in the postal version.This preliminary evaluation indicates that the scales of the GPAQ are internally reliable and that the items demonstrate an interpretable factor structure. Issues concerning the distributions of GPAQ responses are discussed. Potential further developments of the item content for the GPAQ are also outlined.